Polarization of Λ and Λ̄ Hyperons along the Beam Direction in Pb-Pb Collisions at √ˢɴɴ = 5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; Akindinov, A.; et al. (American Physical Society, 2022)
The polarization of the Λ and Λ̄ hyperons along the beam (z) direction, Pz, has been measured in Pb-Pb collisions at √ˢɴɴ = 5.02 TeV recorded with ALICE at the Large Hadron Collider (LHC). The main contribution to Pz comes from elliptic flow-induced vorticity and can be characterized by the second Fourier sine coefficient Pz¸s2 = ⟨Pz sin(2φ − 2Ψ2) ⟩, where φ is the hyperon azimuthal emission angle and Ψ2 is the elliptic flow plane angle. We report the measurement of Pz¸s2 for different collision centralities and in the 30%–50% centrality interval as a function of the hyperon transverse momentum and rapidity. The Pz¸s2 is positive similarly as measured by the STAR Collaboration in Au-Au collisions at √ˢɴɴ = 200 GeV, with somewhat smaller amplitude in the semicentral collisions. This is the first experimental evidence of a nonzero hyperon Pz in Pb-Pb collisions at the LHC. The comparison of the measured Pz¸s2 with the hydrodynamic model calculations shows sensitivity to the competing contributions from thermal and the recently found shear-induced vorticity, as well as to whether the polarization is acquired at the quark-gluon plasma or the hadronic phase.
Keywords: Physics; https://purl.org/pe-repo/ocde/ford#1.03.00